Oral health and salivary function in ulcerative colitis patients. Issue 9 (November 2020) - Goldinova, Ariana; Tan, Christopher XW; Bouma, Gerd; Duijvestein, Marjolijn; Brand, Henk S; de Boer, Nanne K
Background: Although ulcerative colitis primarily involves the colon, extra-intestinal manifestations are common and oral and dental complaints are no exception. Objective: This study aims at evaluating oral and dental health problems and salivary function and composition in ulcerative colitis patients and its correlation with disease activity. Methods: Xerostomia Inventory score, (unstimulated/stimulated) salivary flow rates, salivary amylase and mucin/ Mucin 5B levels, self-reported oral and dental complaints, the oral health related quality of life, Simple Clinical Colitis Activity Index and inflammatory bowel disease-specific health related quality of life were determined. Results: The cohort consisted of 51 ulcerative colitis patients. Hyposalivation was experienced by 16% of patients under resting conditions and 24% under chewing-stimulated conditions. Xerostomia was not correlated with salivary flow rates. Disease activity did not influence salivary amylase and Mucin 5B concentrations. The Xerostomia Inventory score was correlated with the Simple Clinical Colitis Activity Index ( p  = 0.042) and inflammatory bowel disease-specific health related quality of life ( p  = 0.001). Most reported oral health problems were halitosis (29%) and aphthae (28%). Frequently reported dental problems were cavities (35%) and gum problems (31%). Patients with active disease experienced significantly more oral and dental complaints. The number of oral problems was positively correlated with the Simple Clinical Colitis Activity Index ( p  = 0.045) and negatively correlated with the inflammatory bowel disease-specific health related quality of life ( p  = 0.005). Conclusion: The subjective feeling of a dry mouth (xerostomia) is related to disease activity and disease activity-associated quality of life in ulcerative colitis patients, whereas the objective saliva secretion rate is not. Oral and dental health problems are frequently observed in patients with ulcerative colitis, especially during active disease.